2017
DOI: 10.1007/s00213-017-4670-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sustained attention, false alarm responding and implementation of conditional rules by prefrontal GABAA transmission: comparison with NMDA transmission

Abstract: These findings highlight a key role for PFC GABA transmission in reducing sensitivity to distractors during attentional performance. Furthermore, they reveal that disruption of GABA signaling can interfere with the ability to implement conditional rules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
3
8
0
Order By: Relevance
“…Rodent models support the hypothesis that GABA dysfunction contributes to cognitive and social deficits observed in psychiatric conditions such as schizophrenia, autism and depression. Indeed, inhibition of cortical GABA A receptors causes impairments in attention [12,13,14,15], social behavior [16], set-shifting [17], working memory [18] and rewardrelated decision making [19]. These findings support a role for cortical GABA A receptors contributing to the cognitive deficits observed in psychiatric illness.…”
Section: Introductionmentioning
confidence: 80%
“…Rodent models support the hypothesis that GABA dysfunction contributes to cognitive and social deficits observed in psychiatric conditions such as schizophrenia, autism and depression. Indeed, inhibition of cortical GABA A receptors causes impairments in attention [12,13,14,15], social behavior [16], set-shifting [17], working memory [18] and rewardrelated decision making [19]. These findings support a role for cortical GABA A receptors contributing to the cognitive deficits observed in psychiatric illness.…”
Section: Introductionmentioning
confidence: 80%
“…Other labs have demonstrated that acute MK-801 ( Howe and Burk, 2007 ; Rezvani et al, 2009 ; Levin et al, 2014 ) or ketamine treatment ( Hillhouse et al, 2015 ) induces similar VSDT impairments. Furthermore, several labs have demonstrated similar MK-801-induced impairments in alternate behavioral attention models after either systemic ( Auger et al, 2017 ) or intra-cerebral microinjection into the mPFC ( Auger et al, 2017 ), or the anterior cingulate cortex ( Pehrson et al, 2013a ).…”
Section: Discussionmentioning
confidence: 99%
“…In behavioral attention measures such as the 3 choice serial reaction time (3CSRT) task, electrophysiological data demonstrates that the anterior cingulate cortex (ACC) and medial prefrontal cortex (mPFC) play a role in representing attention-relevant information in rats ( Totah et al, 2009 ), and intra-ACC MK-801 injections selectively increased omissions in the 3CSRT task without altering the accuracy ( Pehrson et al, 2013a ). In the sustained attention task, intra-mPFC MK-801 injections impaired vigilance during high-difficulty conditions ( Auger et al, 2017 ). We could not find any study that evaluated non-competitive NMDA receptor antagonists in the VSDT using region-specific microinjections; thus, it is unknown whether these effects translate to this attention model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that inhibiting cortical GABA A receptors causes impaired attention [ 16 , 193 197 ], social behavior [ 198 ], and decision-making [ 199 ]. Recently, it has been demonstrated that mice models having impaired 5-alpha GABA A receptors were presented with behavioral deficits like symptoms associated with attention and social disorders [ 194 ].…”
Section: Gaba a Receptor Dysfunction And Neuro-psychiatric Disordersmentioning
confidence: 99%